Apical role for BRG1 in cytokine-induced promoter assembly - Zuyao Ni; Elizabeth Karaskov; Tao Yu; Steven M. Callaghan; Sandy Der; David S. Park; Zhaodong Xu; Samantha G. Pattenden; Rod Bremner (2005)
IFN-gamma induction of the CIITA (class II transactivator) promoter (pIV) requires Brahma-related gene 1 (BRG1), a chromatin-remodeling enzyme. However, the events that lead to pIV activation are only partially understood, and the point at which BRG1 acts is unknown. The first IFN-gamma-induced event triggers nuclear translocation of STAT1 (signal transducer and activator of transcription 1), which binds IFN-gamma-responsive promoters. BRG1 is recruited after activator binding at several other inducible loci, and STAT family members are known to bind BRG1, suggesting that BRG1 might act downstream of STAT1. Here, we delineate a comprehensive view of factor assembly and detailed histone modifications at pIV and show that all events, even STAT1 binding, require BRG1 at CIITA pIV and other IFN-gamma target promoters. Recruitment of IFN-stimulated gene factor-3 (ISGF3) [STAT1/STAT2/IFN regulatory factor 9 (IRF9)] to several IFN-alpha-responsive promoters is also BRG1-dependent. In contrast, constitutive BRG1 association at IFN targets is STAT1-independent. Furthermore, BRG1 is required for IFN-induced restriction enzyme and DNase I accessibility at promoters. Thus, BRG1 has an apical role in cytokine-induced promoter assembly, acting upstream of STAT complexes at multiple IFN target loci.